The impact of time pressure on decision-making and visual search characteristics in basketball players - Guo, Zhi; Wang, Qiulin (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the effects of time pressure on decision-making and visual search behavior among college basketball players with different levels of expertise.MethodsFollowing the expert–novice paradigm, a total of 40 male participants were recruited, including 20 trained basketball athletes and 20 non-athlete college students. A 2 × 2 mixed factorial design was employed, with athletic expertise (athletes vs. non-athletes) as the between-subjects factor and time pressure (present vs. absent) as the within-subjects factor. Participants were presented with video clips from real basketball games. In the time pressure condition, they were required to make a decision—based on the actions of actual players in the video—within a limited time frame and complete a stress perception questionnaire. In the no time pressure condition, no time constraints were imposed. Decision-making performance (response time and accuracy) and eye-tracking metrics were recorded and analyzed.Results(1) The expert group demonstrated significantly faster response times and higher decision-making accuracy compared to the novice group. (2) In terms of eye-tracking metrics, the expert group exhibited fewer fixations but significantly more saccades and longer fixation durations than the novice group. These findings suggest that experts engage in more focused and efficient visual processing with deeper cognitive engagement. (3) Analysis of fixation distribution and saccade trajectories revealed that experts concentrated more on key informational cues, with tighter and more centralized visual attention patterns, whereas novices showed more scattered and unfocused gaze behaviors.Conclusion(1) Significant differences in visual search strategies were observed between athletes of different skill levels. Experts displayed more efficient search patterns, quicker responses, and superior decision-making performance. (2) Under time pressure, experts maintained high decision accuracy despite faster response times, and their eye movement patterns remained stable, indicating strong adaptability to stress. (3) In contrast, novices showed a marked decline in accuracy and visual search efficiency under time pressure, suggesting weaker cognitive control in high-stress situations.